Successful management of left main coronary artery thrombus with intracoronary thrombolysis - Ufuk Gürkan; Mustafa Adem Tatlısu; Emre Aruğaslan; Osman Bolca (KARE Publishing, 2014)
The management of valvular heart diseases with mechanical valves has been performed for several years. Warfarin has been used in patients with mechanical heart valves to protect against thromboembolic complications; nevertheless, in these patients, thromboembolic event rates range from 0.5% to 1.7%. Acute occlusive embolism to the coronary arteries due to a mechanical valve is an uncommon occurrence. In this report, we present a case of a left coronary system occlusion due to thrombus embolization from a prosthetic aortic valve, which was successfully treated by thrombolytic therapy.